The ‘side effects’ of digitalization: A study on role overload and job burnout of employees - Zhang, Quanjun; Dai, Wei; Chen, Jian; Gu, Yuan; Zhao, Yang (PLOS ONE, 2025)
In the context of the digital economy, enterprise digitalization represents a significant opportunity to enhance core competitiveness. Nevertheless, the digitalization of enterprises may have unanticipated effects on employee’s mental health, which could impede the digital advancement of the enterprise. Such consequences may be evidenced by employee role overload and burnout, which in turn impede enterprise digitalization. This study employed the JR-D model to investigate the empirical data obtained from 250 completed questionnaires by employees. The results indicated that (1) enterprise digitalization had a positive effect on young employees’ levels of role overload and burnout; (2) employees’ role overload served as a mediator between enterprise digitalization and burnout; (3) perceived organizational support moderated the direct predictive effect of enterprise digitalization on burnout and the indirect predictive effect of enterprise digitalization on burnout through role overload, respectively. The higher the level of perceived organizational support, the weaker the direct and indirect predictive effects would be. This study proposed measures and recommendations to mitigate the unintended consequences of digitalization and promote optimal advancement of enterprise digitalization.